Treatment of Schizophrenia With Long-Acting Fluphenazine, Haloperidol, or Risperidone - Olfson, Mark (Oxford University Press, 2007)
Objective: This study compares 3 cohorts of patients with schizophrenia before, during, and after initiating treatment with fluphenazine decanoate (FD), haloperidol decanoate (HD), or long-acting injectable risperidone (LAR). Methods: Administrative data are analyzed from California Medicaid (Medi-Cal) beneficiaries with schizophrenia who initiated FD, HD, or LAR treatment. Patients were required to have been continuously enrolled in Medi-Cal for 180 days before and 180 days after the start of the new episode of long-acting antipsychotic therapy. Results: There were few demographic and clinical differences among patients initiating FD, HD, and LAR. During the 180 days before starting long-acting injections, most patients initiating FD (53.5%), HD (58.5%), and LAR (61.2%) received oral antipsychotic medications for <80% of the days in this period (medication possession ratio: <0.80). The mean duration of depot treatment episodes was 58.3 days (SD = 53.6) for FD, 71.7 days (SD = 56.4) for HD, and 60.6 days (SD = 48.8) for LAR (F = 18.3, df = 2, 2694, P < .0001, HD > FD). Few patients who started on FD (5.4%), HD (9.7%), or LAR (2.6%) continued for at least 180 days. Most patients in each group (FD [77.4%], HD [78.9%], and LAR [75.5%]) received oral antipsychotic medications during the 45 days after discontinuing long-acting injections. Coprescription with antidepressants, mood stabilizers, and benzodiazepines was common. Conclusions: Patients treated with long-acting antipsychotic injections tend to have complex pharmacological regimens and recent medication nonadherence. A great majority of patients initiating long-acting antipsychotic medications discontinue use within the first few months of treatment.